2011
DOI: 10.1590/s0103-84782011005000077
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico de criptosporidiose em amostras fecais de bezerros por imunofluorescência direta e microscopia de contraste de fase

Abstract: O presente estudo teve como objetivo comparar as técnicas de imunofluorescência direta (IFD) e a microscopia de contraste de fase em solução de Sheather (MCF), para detecção de oocistos de Cryptosporidium spp. em amostras fecais de bezerros. A determinação dos limiares detecção da IFD e da MCF foi realizada utilizando cinco alíquotas de uma amostra fecal de bezerro, comprovadamente negativa para Cryptosporidium spp., adicionadas com diferentes quantidades de oocistos de Cryptosporidium parvum. Ao exame das 5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…The diagnostic methods using microscopy that are most used and least expensive involve screening for oocysts after centrifugal flotation in Sheather's solution, followed by phase contrast microscopy (Figure 3b) or bright-field microscopy (CARDOZO et al, 2008;TEIXEIRA et al, 2011a) and any of the many staining techniques for fecal samples, including negative malachite green staining (Figure 3c) (ELLIOT et al, 1999) and acid-fast staining (HENRIKSEN & POHLENZ, 1981;ORTOLANI, 2000;CARDOZO et al, 2008). In morphometric studies, morphological and morphometric alterations in oocysts should be considered when fecal smears are subjected to staining techniques (MEIRELES & FIGUEIREDO, 1992;CARDOZO et al, 2005).…”
Section: Diagnosis Of Cryptosporidiosis Among Birdsmentioning
confidence: 99%
“…The diagnostic methods using microscopy that are most used and least expensive involve screening for oocysts after centrifugal flotation in Sheather's solution, followed by phase contrast microscopy (Figure 3b) or bright-field microscopy (CARDOZO et al, 2008;TEIXEIRA et al, 2011a) and any of the many staining techniques for fecal samples, including negative malachite green staining (Figure 3c) (ELLIOT et al, 1999) and acid-fast staining (HENRIKSEN & POHLENZ, 1981;ORTOLANI, 2000;CARDOZO et al, 2008). In morphometric studies, morphological and morphometric alterations in oocysts should be considered when fecal smears are subjected to staining techniques (MEIRELES & FIGUEIREDO, 1992;CARDOZO et al, 2005).…”
Section: Diagnosis Of Cryptosporidiosis Among Birdsmentioning
confidence: 99%
“…negative malachite green staining (Elliot et al, 1999), safranin methylene blue (Garcia, 2007(Garcia, , 2009 and trichrome (Garcia, 2007(Garcia, , 2009. Other techniques can also be used for this diagnostic purpose, such as phase contrast microscopy (Teixeira et al, 2011), direct fluorescent antibody test (CDC, 2015) and enzyme-linked immunosorbent assay (CDC, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…were found in 100% of the analyzed calves, using the Ziehl-Neelsen modified method (Almeida et al, 2008). Teixeira et al (2011) also reported 100% of the animals parasitized by this protozoan in a study in the state of São Paulo.…”
Section: Results and Discusionmentioning
confidence: 90%